IMPLEMENTASI KEBIJAKAN PENYELENGGARAAN IBADAH HAJI DI KOTA BANDUNG TAHUN 2018 - Ahmad Syamsir (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
This research is motivated by the phenomena of policy in the implementation of the Hajj pilgrimage which every year there is always a change in the Ministry of Religion of Bandung City as the representative of the central government with the intention to facilitate and make the smooth running of the Hajj. However, in the development of provisions for guidance, services and protection for pilgrims have not been carried out as stated in Law No. 13 of 2008. In reality there is a contradiction in the implementation of the pilgrimage that the rights and responsibilities of pilgrims are more burdened to the pilgrimage guidance group (KBIH ), however, the role of KBIH is still neglected, the government pays more attention to the orientation of success and fluency only with limited human resources in the implementation of the pilgrimage in general, without regard to service, guidance and protection by providing facilities, facilities, security and comfort needed by pilgrims pilgrimage.